2024
DOI: 10.1111/beer.12671
|View full text |Cite
|
Sign up to set email alerts
|

The effect of government informatization construction on corporate digital technology innovation: New evidence from China

Yuan Feng,
Changfei Nie

Abstract: This study explores the impact of government informatization construction on corporate digital technology innovation. It uses the integration of informatization and industrialization pilot zones in China as a quasi‐natural experiment of government informatization construction, and construct a difference‐in‐differences model. Based on a sample of Chinese A‐share corporations from 2007 to 2021, the empirical findings reveal that government informatization construction significantly promotes corporate digital tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
2
3
0
Order By: Relevance
“…As we can see, the estimated coefficients of Pilot * Time × IPP in columns ( 1)-( 3) are all significantly positive at the 1% level, indicating that urban intellectual property protection intensity is a positive moderator in the promotion of urban GI by the NEEC. This result is consistent with Feng and Nie's description of the role of intellectual property protection in urban GI on Broadband Infrastructure Construction [49].…”
Section: The Moderating Role Of Intellectual Property Protectionsupporting
confidence: 91%
See 1 more Smart Citation
“…As we can see, the estimated coefficients of Pilot * Time × IPP in columns ( 1)-( 3) are all significantly positive at the 1% level, indicating that urban intellectual property protection intensity is a positive moderator in the promotion of urban GI by the NEEC. This result is consistent with Feng and Nie's description of the role of intellectual property protection in urban GI on Broadband Infrastructure Construction [49].…”
Section: The Moderating Role Of Intellectual Property Protectionsupporting
confidence: 91%
“…However, using the PSM method, we can match each experimental group sample to a specific control group sample, making the quasi-natural experiment approximate randomization. To overcome the selection bias problem, we employ the PSM-DID method to estimate the effect of the NEEC policy on GI [49]. Specifically, the dependent variable is used as the result variable, the six control variables are used as the matching variables, and the nearest neighbor matching method is used to fit the control and experimental city samples.…”
Section: Propensity Score Matching (Psm)-did Testmentioning
confidence: 99%
“…This suggests that the level of intellectual property protection positively mediates the relationship between the digital economy and green innovation efficiency. This is similar to the findings of Fen and Nie (2024), who reported that intellectual property protection plays a crucial role in moderating the effect of digitalization on technological innovation, enabling synchronized development between the two [51]. A possible reason for this is that continuously improving the level of intellectual property protection during the R&D stage of green innovation technology can effectively stimulate enterprise enthusiasm for independent innovation, enhance the expected returns of green innovation investments, and contribute to the formation of a new pattern of technology and knowledge sharing, thus radiating and driving the green development of neighboring regions.…”
Section: Moderating Effects Of Intellectual Property Protectionsupporting
confidence: 91%
“…To further eliminate the differences in control variables related to ECER demonstration cities, we refer to Hainmueller to construct the entropy balancing method for testing, which has more advantages than PSM [61]. This method makes the probability score between the control and experimental groups similar without causing sample loss [62]. The coefficients of ECER remain significantly negative after using the samples processed by the entropy balancing method (see Table 5), providing additional evidence that the ECER policy effectively reduces both TCEs and CEI.…”
Section: Entropy Balancing Methodsmentioning
confidence: 99%